PERTIKAIAN SOSIAL ANTARA PEMULUNG (STUDI PADA PEMULUNG ETNIS BATAK DI KECAMATAN TAMPAN KOTA PEKANBARU) - Simanjuntak, Viorentina; ", Yoserizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted in Kecamatan Tampan Pekanbaru City. The purpose of this research is to know the characteristics of Batak ethnic scavengers in Kecamatan Tampan Pekanbaru City, to know the forms of social disputes in Kecamatan Tampan Pekanbaru City. The focus of this research is about the factors that trigger the controversy between fellow scavengers in Kecamatan Tampan Pekanbaru City. The technique of determining the sample by purposive sampling. and set the number of samples as many as 5 people. The author uses quantitative descriptive method and Instrument data is observation, interview and documentation. The study found some characteristics of scavengers in Kecamatan Tampan as follows: Quantity Working Time: The study found that the average of research subjects started doing scavenging activity from morning at 5.30 to evening. Working System: The study found that generally the research subjects only scavenged in some places that are believed to be fixed locations scavenge every day. Revenue: Before becoming a scavenger the average research subjects only have income as much as Rp 300.000-1.200.000 / month, but after being a scavenger the average research subject is able to collect income as much as Rp> 2.000.000 / bulan. Barriers to Scavenging: Some of the obstacles experienced by research subjects in work are like experiencing work disorder such as dislocated legs and damaged scavenger tools and the availability of used goods that are sought. The research also found that there were some forms of dispute between the scavengers in Kecamatan, as follows: Working Area Problems: The problem of this working area was found in a dispute involving three research subjects, Rona's mother, Mr Rehat and Mrs. Sondang. Problem Type of Goods Collected: The problem of this type of goods collected involves four research subjects. Namely Rona's mother, father Kamal, father Yanto and father break. Keywords: Conflict, Social Dispute, Scavenger